Scaling predictions for radii of weakly bound triatomic molecules - Yamashita, M. T.; Marques de Carvalho, R. S. [UNESP]; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 2003)
The mean-square radii of the molecules [Formula Presented] [Formula Presented] [Formula Presented] and [Formula Presented] are calculated using a three-body model with contact interactions. They are obtained from a universal scaling function calculated within a renormalized scheme for three particles interacting through pairwise Dirac-[Formula Presented] interaction. The root-mean-square distance between two atoms of mass [Formula Presented] in a triatomic molecule are estimated to be of the order of [Formula Presented] where [Formula Presented] is the dimer and [Formula Presented] is the trimer binding energies, and [Formula Presented] is a constant (varying from [Formula Presented] to [Formula Presented] which depends on the ratio between [Formula Presented] and [Formula Presented] Considering previous estimates for the trimer energies, we also predict the sizes of rubidium and sodium trimers in atomic traps. © 2003 The American Physical Society.